Asked
9 months ago

Viewed
187619 times

**Answer:**

x = 3

x + 3 = 6

√45

**Step-by-step explanation:**

**the general theorem is **

a^2 + b^2 = c^2

**Givens**

a = x

b = x + 3

c = √45

**Solution**

x^2 + (x + 3)^2 = (√45)^2 Substitute

x^2 + x^2 + 6x + 9 = 45 Expand the brackets. Square √45

2x^2 + 6x + 9 = 45 Subtract 45 from both sides

2x^2 + 6x - 36 = 0 Divide by 2

x^2 + 3x - 18 = 0 Factor

(x + 6)(x - 3) = 0 x+ 6 has no meaning in the real world.

x - 3 = 0

x = 3

Answer

a) 3

b) 6

c) √45